If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x = (x + -2)(2x + 4) Reorder the terms: x = (-2 + x)(2x + 4) Reorder the terms: x = (-2 + x)(4 + 2x) Multiply (-2 + x) * (4 + 2x) x = (-2(4 + 2x) + x(4 + 2x)) x = ((4 * -2 + 2x * -2) + x(4 + 2x)) x = ((-8 + -4x) + x(4 + 2x)) x = (-8 + -4x + (4 * x + 2x * x)) x = (-8 + -4x + (4x + 2x2)) Combine like terms: -4x + 4x = 0 x = (-8 + 0 + 2x2) x = (-8 + 2x2) Solving x = -8 + 2x2 Solving for variable 'x'. Reorder the terms: 8 + x + -2x2 = -8 + 2x2 + 8 + -2x2 Reorder the terms: 8 + x + -2x2 = -8 + 8 + 2x2 + -2x2 Combine like terms: -8 + 8 = 0 8 + x + -2x2 = 0 + 2x2 + -2x2 8 + x + -2x2 = 2x2 + -2x2 Combine like terms: 2x2 + -2x2 = 0 8 + x + -2x2 = 0 Begin completing the square. Divide all terms by -2 the coefficient of the squared term: Divide each side by '-2'. -4 + -0.5x + x2 = 0 Move the constant term to the right: Add '4' to each side of the equation. -4 + -0.5x + 4 + x2 = 0 + 4 Reorder the terms: -4 + 4 + -0.5x + x2 = 0 + 4 Combine like terms: -4 + 4 = 0 0 + -0.5x + x2 = 0 + 4 -0.5x + x2 = 0 + 4 Combine like terms: 0 + 4 = 4 -0.5x + x2 = 4 The x term is x. Take half its coefficient (0.5). Square it (0.25) and add it to both sides. Add '0.25' to each side of the equation. -0.5x + 0.25 + x2 = 4 + 0.25 Reorder the terms: 0.25 + -0.5x + x2 = 4 + 0.25 Combine like terms: 4 + 0.25 = 4.25 0.25 + -0.5x + x2 = 4.25 Factor a perfect square on the left side: (x + 0.5)(x + 0.5) = 4.25 Calculate the square root of the right side: 2.061552813 Break this problem into two subproblems by setting (x + 0.5) equal to 2.061552813 and -2.061552813.Subproblem 1
x + 0.5 = 2.061552813 Simplifying x + 0.5 = 2.061552813 Reorder the terms: 0.5 + x = 2.061552813 Solving 0.5 + x = 2.061552813 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-0.5' to each side of the equation. 0.5 + -0.5 + x = 2.061552813 + -0.5 Combine like terms: 0.5 + -0.5 = 0.0 0.0 + x = 2.061552813 + -0.5 x = 2.061552813 + -0.5 Combine like terms: 2.061552813 + -0.5 = 1.561552813 x = 1.561552813 Simplifying x = 1.561552813Subproblem 2
x + 0.5 = -2.061552813 Simplifying x + 0.5 = -2.061552813 Reorder the terms: 0.5 + x = -2.061552813 Solving 0.5 + x = -2.061552813 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-0.5' to each side of the equation. 0.5 + -0.5 + x = -2.061552813 + -0.5 Combine like terms: 0.5 + -0.5 = 0.0 0.0 + x = -2.061552813 + -0.5 x = -2.061552813 + -0.5 Combine like terms: -2.061552813 + -0.5 = -2.561552813 x = -2.561552813 Simplifying x = -2.561552813Solution
The solution to the problem is based on the solutions from the subproblems. x = {1.561552813, -2.561552813}
| 4x+8y=16 | | 7x+3=2x-4 | | 4x+1=6x-7 | | 2x+8-15=45 | | 2x+8-25=45 | | 2(4n+8)= | | (5)10-(5)13= | | -6x=80 | | a-z=-5(39-a)-3 | | 171-3x=24x+18 | | x^2-16x+64=3 | | x=2*x-4 | | x^2+2x+1=49 | | y=30+11y | | 3x+2b=x+8 | | x=x-2*2x-4 | | 9x^2-14x-8=0 | | x^2+20x-3=0 | | 56753366x=786556 | | 9x^2+65x+14=0 | | a=12a-44 | | x=(x-2)*(2x-4) | | 5x^2+38x+21=0 | | x^2+18x+90=0 | | x^2+18+90=0 | | 20x+35=0 | | 6x+20=3x+11 | | x=x-2*(4) | | x=4*(x-2) | | x=2*x+1-(2*2+1) | | (x-7)(2x+9)=0 | | x=x-2*(2) |